2017
DOI: 10.2337/dc17-1150
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and All-Cause Mortality Risk Associated With Urinary Excretion of 8-oxoGuo, a Biomarker for RNA Oxidation, in Patients With Type 2 Diabetes: A Prospective Cohort Study

Abstract: We conclude that high RNA oxidation is associated with all-cause and cardiovascular mortality risk in patients with type 2 diabetes. Targeting oxidative stress via interventions with long-term follow-up may reveal the predictive potential of the biomarker 8-oxoGuo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…In the ADVANCE prospective trial, increased levels of 8-OHdG were independently associated with all-cause and cardiovascular mortality in 3766 T2DM [95]. In a recent prospective cohort study involving 1863 patients with T2DM, 8-oxoGuo was associated with all-cause mortality and cardiovascular death after multiple regression analysis [96]. Moreover, recent findings suggest that urinary 8-oxoGuo provides additional information about risk to that obtained from urinary albumin and that the combined use of 8-oxoGuo and urinary albumin could be useful for a better identification of patients at risk of CVD and death over a period of 19 years of follow-up [97] (Table 3).…”
Section: Biomarkers Of Oxidative Dna and Rna Damagementioning
confidence: 99%
“…In the ADVANCE prospective trial, increased levels of 8-OHdG were independently associated with all-cause and cardiovascular mortality in 3766 T2DM [95]. In a recent prospective cohort study involving 1863 patients with T2DM, 8-oxoGuo was associated with all-cause mortality and cardiovascular death after multiple regression analysis [96]. Moreover, recent findings suggest that urinary 8-oxoGuo provides additional information about risk to that obtained from urinary albumin and that the combined use of 8-oxoGuo and urinary albumin could be useful for a better identification of patients at risk of CVD and death over a period of 19 years of follow-up [97] (Table 3).…”
Section: Biomarkers Of Oxidative Dna and Rna Damagementioning
confidence: 99%
“…The ADVANCE Trial revealed that 8-oxo-2'-deoxyguanosine levels were correlated with all-cause and cardiovascular mortality in adults with type 2 diabetes mellitus (T2DM) (n = 3766) [110]. Likewise, an independent prospective cohort study revealed a correlation of RNA oxidation with all-cause and cardiovascular mortality risk in patients with T2DM [111]. Dapagliflozin therapy conferred better glycemic control, endothelial function, which was associated with lower 8-oxo-2'-deoxyguanosine urine levels in T2DM patients [112].…”
Section: Clinical Evidence For a Role Of Oxidative Stress In Cardiovamentioning
confidence: 99%
“…Increased levels of oxidative stress may predict mortality in patients with other chronic diseases such as diabetes 35 . Epidemiological studies have found that the life expectancy among patients with BD is decreased by 8–12 years compared to the general population 36 and that patients die due to natural causes of death already from adolescence 37 .…”
Section: Discussionmentioning
confidence: 99%